Comparison of the Asymmetries in Foot Posture and Properties of Gastrocnemius Muscle and Achilles Tendon Between Patients With Unilateral and Bilateral Knee Osteoarthritis - Chen, Zehua; Ye, Xiangling; Shen, Zhen; Wang, Yi; Wu, Zugui; Chen, Guoqian; Guan, Yingxin; Wu, Jiatao; Jiang, Tao; Wu, Huai; Liu, Wengang; Xu, Xuemeng (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Asymmetrical foot posture and properties alterations of the gastrocnemius muscle (GM) and Achilles tendon (AT) were observed in knee osteoarthritis (KOA). We aimed to investigate the inter-limbs asymmetries in foot posture and the properties of GM and AT and explore the association between them. Methods: A total of 62 subjects with unilateral or bilateral KOA were included in this study: 30 patients with unilateral pain and 32 patients with bilateral pain were assigned to the bilateral group (BG) and unilateral group (UG), respectively. The relatively serious leg (RSL) and relatively moderate leg (RML) were judged according to the severity of symptoms assessed by using visual analogue scale (VAS) motion. Foot posture and asymmetrical foot posture scores were assessed based on Foot Posture index (FPI-6). Subsequently, all the participants received an assessment for properties of GM and AT, including tone/tension (Hz), stiffness (N/m), and elasticity. We calculated the asymmetry index of AT (Asy-AT) in both legs and the difference of muscle properties between medial and lateral gastrocnemius (D-MLG) in the ipsilateral limb. Results: Asymmetry of foot posture was categorized into three types including normal, asymmetry, and severe asymmetry. The percentage of subjects classified as normal was higher in the BG (62.5%) than in the UG (36.67%), p < 0.05. Tension of AT and tone of lateral gastrocnemius (LG) in RSL were higher than those in RML (15.71 ± 0.91 vs. 15.23 ± 1.01; 25.31 ± 2.09 vs. 23.96 ± 2.08, p < 0.01 and p < 0.01, respectively), and stiffness of AT in the RSL was higher than that in RML (676.58 ± 111.45 vs. 625.66 ± 111.19, p < 0.01). Meanwhile, a positive relationship was found between ipsilateral FPI and tone of MG and LG in the left leg (0.246 per degree, 95% CI: −0.001, 0.129; p = 0.054 and 0.293 per degree, 95% CI: −0.014, 0.157; p = 0.021, respectively) and right leg (0.363 per degree, 95% CI: 0.033, 0.146; p = 0.004 and 0.272 per degree, 95% CI: 0.007, −0.144; p = 0.032, respectively). Moreover, a positive link was observed between asymmetrical FPI scores and K/L grade (0.291 per degree, 95% CI: 0.018, 0.216; p = 0.022). Furthermore, a significantly greater Asy-AT(tension) was detected in the UG than that in the BG (UG vs. UG: 8.20 ± 5.09% vs. 5.11 ± 4.72%, p < 0.01). Additionally, an increased asymmetrical FPI score (i.e., more severe asymmetry) was significantly associated with increases in Asy-AT(tension) and Asy-AT(stiffness) (0.42 per degree, 95% CI: 0.533, 1.881; p = 0.001 and 0.369 per degree, 95% CI: 0.596, 2.82; p = 0.003, respectively). Conclusions: The stiffness and tension of AT and the tone of LG in RSL were higher than those in RML in KOA patients, and inter-limbs foot posture and tension of AT were more asymmetrical in unilateral KOA patients compared to patients with bilateral KOA. Notably, foot posture, as an important biomechanical factor, was significantly associated with properties of GM, AT, and K/L grade in KOA patients.